2021
DOI: 10.1128/iai.00787-20
|View full text |Cite
|
Sign up to set email alerts
|

The Diadenylate Cyclase CdaA Is Critical for Borrelia turicatae Virulence and Physiology

Abstract: Relapsing fever (RF), caused by spirochetes of the genus Borrelia, is a globally distributed, vector-borne disease with high prevalence in developing countries. To date, signaling pathways required for infection and virulence of RF Borrelia spirochetes are unknown. Cyclic di-AMP (c-di-AMP), synthesized by diadenylate cyclases (DACs), is a second messenger predominantly found in Gram-positive organisms that is linked to virulence and essential physiological processes. Although Borrelia is Gram-negative, it enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 162 publications
(405 reference statements)
0
22
0
Order By: Relevance
“…Loss of the c-di-AMP synthesizing enzymes is lethal to the bacterial cell ( 7 ). Since its discovery in 2008, numerous studies have reported the presence of c-di-AMP in a wide range of different bacterial species, of which several are well-known human pathogens, for example, Listeria monocytogenes , Mycobacterium tuberculosis , Borrelia turicatea , Enterococcus faecium , Staphylococcus aureus , and Streptococcus pneumoniae ( 22 , 23 , 24 ). With the exception of M. tuberculosis , these bacteria use the diadenylate cyclase CdaA as the sole enzyme responsible for c-di-AMP synthesis.…”
mentioning
confidence: 99%
“…Loss of the c-di-AMP synthesizing enzymes is lethal to the bacterial cell ( 7 ). Since its discovery in 2008, numerous studies have reported the presence of c-di-AMP in a wide range of different bacterial species, of which several are well-known human pathogens, for example, Listeria monocytogenes , Mycobacterium tuberculosis , Borrelia turicatea , Enterococcus faecium , Staphylococcus aureus , and Streptococcus pneumoniae ( 22 , 23 , 24 ). With the exception of M. tuberculosis , these bacteria use the diadenylate cyclase CdaA as the sole enzyme responsible for c-di-AMP synthesis.…”
mentioning
confidence: 99%
“…Cells were then lysed using a CF1 cell disrupter (Constant Systems Ltd., Daventry, UK). Following cell lysis, recombinant InvL was purified from the insoluble fraction by Ni-nitrilotriacetic acid affinity chromatography as previously described ( 107 ). Purified protein was then used by Antibody Research Corporation (St. Peters, MO) to generate polyclonal rabbit antibody.…”
Section: Methodsmentioning
confidence: 99%
“…To generate soluble recombinant InvL for ELISA (described below), InvL lacking the N-terminal signal sequence (as determined by SignalP 5.0) was expressed with a C-terminal His 10 tag from pET-22b(+):: invL-his 10 (-SS) in Rosetta-gami 2(DE3) cells by addition of 1 mM isopropyl-β- d -thiogalactopyranoside for 3 h at 37°C ( 41 ). Cells were then lysed as described above, and recombinant InvL was purified from the soluble fraction using the procedure previously described with the exception that buffers were not supplemented with 0.3% N -lauryl-sarcosine ( 107 ).…”
Section: Methodsmentioning
confidence: 99%
“…To generate soluble recombinant InvL for ELISAs (see below), InvL lacking the N-terminal signal sequence (as determined by SignalP 5.0) was expressed with a C-terminal His10 tag from pET-22b(+)::invL-his10(-SS) in Rosetta-gami 2(DE3) cells by addition of 1 mM isopropyl-β-d-thiogalactopyranoside for 3 hrs at 37°C (41). Cells were then lysed as above, and recombinant InvL was purified from the soluble fraction using the same procedure as previously described with the exception that buffers were not supplemented with 0.3% N-lauryl-sarcosine (104).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were then lysed using a CF1 cell disrupter (Constant Systems Ltd, Daventry, UK). Following cell lysis, recombinant InvL was purified from the insoluble fraction by Ni-NTA affinity chromatography as previously described (104). Purified protein was then used by Antibody Research Corporation (St. Peters, MO) to generate polyclonal rabbit antibody.…”
Section: Murine Infection Experiments Animal Experiments Were Approve...mentioning
confidence: 99%